A messy murder [large type] - Brett, Simon (Brett, Simon. Decluttering mysteries, 2024)
"Professional declutterer Ellen Curtis doesn't need to like her clients to help them sort their homes out. Aging TV personality and curmudgeon Humphrey Carter might have a chip on his shoulder the size of England about the decline of his career, but a job's a job. But when Ellen arrives the morning after Humph's eightieth birthday party, primed and ready to tackle his study...she gets the shock of her life. Humph's dead...and all signs point to him having taken his own life. Did the egotistical chat show host really die by suicide? His wife is adamant he's been murdered, and the more Ellen looks, the more dirt on Humph she digs up...and the more suspects she uncovers. Can she track down a killer--if there even is one? And, just as importantly, can she keep herself from killing not only her own infuriating mother, but also her two grown-up children, who all seem determined to destroy her peace of mind?"--Back cover.